Modeling and Prediction of Long-Distance Traffic Flows Through the Example of Road Transport in the Czech Republic. - Halás, Marián; Kraft, Stanislav (Scottish Geographical Journal, 2016)
The construction of large-scale long-distance roads brings an irreversible impact on the landscape and therefore its careful and precise planning is very important. For this planning we use data on the intensity of traffic flows on existing roads and statistical tools for the modeling of planned traffic flows. The main objective of this paper is the modeling of the existing intensity of traffic flows on highways and expressways in the Czech Republic by determination of the optimal distance-decay function. On the basis of the resulting model and the resulting distance-decay function, it is possible to predict the intensity of traffic in the event of the completion and commissioning of new sections of highways and expressways. The subsequent analysis will allow us to make a qualified prediction of traffic intensity in the event of the completion of the R35 expressway, or after the completion of the R35 and R43 expressways. Besides the intensity on the above-mentioned roads themselves, the paper also predicts the expected reduction in traffic intensity on the busiest highway in the Czech Republic, that is, on the D1 highway between Prague and Brno.